Physics Learning using Inquiry-Student Team Achievement Division (ISTAD) and Guided Inquiry Models Viewed by Students Achievement Motivation - Sulistijo, S. H.; Sukarmin, S.; Sunarno, W. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2017)
This study aims to determine the differences in learning outcomes of between students that are given the Physics learning models of Inquiry-Student Team Achievement Division (ISTAD) and guided inquiry, between students who have high achievement motivation and low achievement motivation. This study was an experimental study with a 2x2x2 factorial design. The study population was the students of class X of SMAN 1 Toroh Grobogan of academic year 2016/2017. Samples were obtained by cluster random sampling technique consists of two classes, class X IPA 3 is used as an experimental class using ISTAD model and class X IPA 4 as the control class using guided inquiry model. Data collection techniques using test techniques for learning outcomes, and technical questionnaire to obtain the data of students' achievement motivation. Analysis of data using two-way ANOVA. The results showed that: (1) there is a difference between the learning outcomes of students with the ISTAD Physics models and with the physics model of guided inquiry. (2) There are differences in learning outcomes between students who have high achievement motivation and low achievement motivation. (3) There is no interaction between ISTAD and guided inquiry Physics models learning and achievement motivation of students.